Bolt connection performance post fire in steel bridges. Issue 2 (April 2020) - Gunadi, R; Moeljono, M; Igustiany, F; Hasan, N
Abstract: Fire events reduce the strength of the steel structure on the bridge and can cause collapse which results in losses, so it is necessary to consider the effects of fire when planning construction. Considering that the joints affect the performance of steel structures, the results of research on the performance of steel beams need to be augmented by testing the post-fire girder bridge bolt connection performance. Structural tests will be carried out on six specimens of bridge steel beam elements with high quality bolt connections in the center of the beam with sliding type bolt connections. Two control specimen beams were tested with shear loads without combustion. Two specimens with temperature of 700°C and 900°C with different torque bond variables. From the displacement control test using UTM on six specimens, it will be known the performance of each type of connection by evaluating changes in carrying capacity, stiffness, deflection capacity, ductility, and stress-strain capacity due to the influence of temperature acting during the fire process. The results can prove which type of bolt connection is better for use on bridges with fire risk.